Influence of patient and hospital characteristics on inpatient satisfaction in China's tertiary hospitals: A cross‐sectional study - LinLin Hu; Hui Ding; Shiyang Liu; Zijuan Wang; Guangyu Hu; Yuanli Liu (Wiley, 2020)
Abstract Background Patient satisfaction has been seen as a key criterion when evaluating hospitals and is one of the main focuses of the current health‐care reform in China. This paper aimed to explore patient‐ and hospital‐level factors associated with inpatient satisfaction, which can provide policy implications for the evaluation and development of a patient‐oriented health‐care system. Methods The paper analyses data from the 2017 China National Patient Survey which includes 20 300 inpatients from 131 tertiary hospitals across 31 provinces. Descriptive analysis and multivariable logistic regressions are conducted to identify key factors related to satisfaction. Results Patient sociodemographic characteristics, including gender, age, income and insurance type, are found to be strongly associated with their satisfaction of inpatient experience. In terms of institutional characteristics, hospital type, size, staffing and financial performance are also significantly correlated with inpatient satisfaction. Patients are more satisfied with specialist hospitals and large hospitals measured by the number of beds and surgeries. Hospitals with higher nurse‐to‐bed ratio also receive more satisfaction. The financial performance of hospitals, however, is negatively associated with satisfaction. Conclusion Patient satisfaction contains unique information on service quality and thus should be incorporated into the matrix of hospital evaluation. Meanwhile, differences in patient composition must be adjusted to make fair comparisons across hospitals. Moreover, future reform needs to put greater efforts in the design of comprehensive public insurance scheme, efficient hospital structure and an overall well‐functioning health‐care delivery system in order to better serve patients in China.